PENYULUHAN ASPEK PEMASARAN DAN PENATAAN (LAYOUT) BARANG DAGANGAN DI TOKO KELOMPOK PENGRAJIN PERALATAN DAPUR DESA KEPATIHAN TULUNGAGUNG JAWA TIMUR - Rulirianto Rulirianto; Bambang Irawan; Heru Utomo (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
Activity partners in PKM activities are a group of craftsmen making kitchenware and a shop as a means of displaying the resulting product. Writing is more emphasis on store activities, especially in the arrangement or layout of merchandise. The location of partner activities is located in Kepatihan Village RW 1, RT 4 Jln. Urip Sumoharjo 26 (PB Sudirman No. 6) Tulungagung.Lack of store merchant knowledge to be able to display their goods so that the impression impressed placement of goods looks chaotic or not organized neatly and well. Understanding Important merchandise layouts get attention so that the condition and structure of the placement do not seem random and sometimes difficult to take the goods, otherwise the placement of good merchandise will make it easier to reach the goods and clean it, so as not to impress the slums. Through the arrangement or placement of regular merchandise will show a neat impression and the room looks spacious and spacious. So that in the end make comfortable both shopkeepers and consumers.Implementation of the introduction of techniques in the way of "Marketing" the practice of structuring goods, namely the first need to grouping the type of goods that have almost the same function. Prepare for display of merchandise, with various considerations, especially the affordability of the goods when taken back. Counseling and mentoring about the need for marketing knowledge, then for the seller to be more wise and wise in serving the prospective buyer or buyer of goods, placement of goods more neat (Layout) and placement tailored to the similarity of usability functions, and the need for mastery of knowledge about products sold.